2012
DOI: 10.1136/bmjopen-2012-000830
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Great East Japan Earthquake and huge tsunami on glycaemic control and blood pressure in patients with diabetes mellitus

Abstract: ObjectiveTo examine the effects of a huge tsunami resulting from the Great East Japan Earthquake on blood pressure (BP) control and glycaemic control in diabetic patients.DesignA retrospective study.SettingTohoku University, Japan.Participants63 patients were visiting Rikuzentakata Hospital for diabetic treatment before the earthquake and returned to the clinic in July after the earthquake, and they were analysed in the present study. The subjects were divided into two groups: those who were hit by the tsunami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 9 publications
3
45
0
Order By: Relevance
“…Of the patients following up in our clinic after the war, 22.1% had been displaced from their homes because of the war, which has been found to be a risk factor for uncontrolled diabetes in other studies [6,13]. In our study, 10% of the patients had lost a first-or seconddegree relative and 8.9% had damage to their homes because of the war.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Of the patients following up in our clinic after the war, 22.1% had been displaced from their homes because of the war, which has been found to be a risk factor for uncontrolled diabetes in other studies [6,13]. In our study, 10% of the patients had lost a first-or seconddegree relative and 8.9% had damage to their homes because of the war.…”
Section: Discussionsupporting
confidence: 48%
“…Studies done in other countries during war have shown different results, with some having an increase in HbA1c during war and others showing no change in diabetes control [5][6][7][8]. There has been a worsening of diabetes control after other disasters, such as extensive flooding [11], earthquakes and tsunamis [12,13]. Additionally, acute psychological stress has been found to cause hyperglycemia in studies in animals and humans [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in blood pressure and aggravation of diabetes mellitus were reported after the Great East Japan earthquake and tsunami. 21,22 This disaster placed many people in northeastern Japan under a great deal of stress because of loss of their families, loss of their homes, life in shelter, lifeline damage, lack of daily necessities, and insufficiency of medical service. Mental stress and environmental changes after disasters caused increased sympathetic nervous activity, elevation of blood pressure, elevation of blood viscosity, increased coagulation function, and platelet activation, and these factors can trigger cardio-and cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of earthquake-associated disease onset or aggravation, cardiovascular disease, respiratory disease, diabetes mellitus, hypertension and peptic ulcer were reported to have increased after the huge earthquake. [12][13][14][15][16][17] However, there has been no report about relapses of IBD caused by the huge earthquake.…”
Section: Introductionmentioning
confidence: 99%